THE IMPORTANCE OF THE DENTAL SURGEON IN DENTAL CARE IN PATIENTS WITH DIABETES MELLITUS - Pereira da Silva, Gizele; Anyelle Pessoa Dias Dantas, Manoelly; Freitas Dantas, Rodolfo (Health and Society, 2021)
Diabetes mellitus (DM) affects a high proportion of the Brazilian population. Various organs are affected, including oral tissues. Thus, the objective of this article is to review the relationship between DM and oral health, highlighting the importance of the dentist’s performance in affected patients. The method used was a literature review using the following databases: LILACS, BBO, SCIELO and Google Scholar, using the keywords: diabetes mellitus, diabetes mellitus and dentistry, dentist and diabetic patients. The method used was a literature review using the following databases: LILACS, BBO, SCIELO and Google Scholar, using the keywords: diabetes mellitus, diabetes mellitus and dentistry, dentist and diabetic patients. As a result, it showed the consensus among studies on the finding that patients with DM have oral problems, gingival and periodontal disease, abnormalities in the composition of saliva, among others. Regarding caries in diabetics, there is no unanimity, some studies confirm the increase in caries in this group, in others this relationship is not significant. The study shows that dental control is paramount in the treatment and prevention of DM. Oral health education can minimize the risks caused by this pathology. The well-prepared dentist can contribute to the prevention and early diagnosis of diabetes complications, an essential factor for a good treatment of the disease and a better quality of life for these individuals.